Institutional Management of Islamic Education in the Governance of Madrasah Diniyah Takmiliyah Awaliyah Al-Ikhlas Damsari - HIKMAH, IQLIMA AVIATUL; Hanif, Muh (JIEM (Journal of Islamic Education Management), 2025)
The institutional management of Islamic education, especially Madrasah Diniyah Takmiliyah Awaliyah (MDTA), is a management process that involves planning, organizing, implementing, and supervising human resources and non-human resources in order to achieve Islamic education goals effectively and efficiently. One of them is Madrasah Diniyah Takmiliyah Awaliyah Al-Ikhlas, a non-formal institution that has its own foundation in Damsari Village, Paguyangan District, Brebes Regency. This study aims to describe the institutional management of Islamic education in the governance of Madrasah Diniyah Takmiliyah Awaliyah Al-Ikhlas Damsari. This article uses qualitative research with data collection techniques in the form of documentation, interviews, and observations. The results of the study show that institutional management in Madrasah Al-Ikhlas is fully held by the head of the Madrasah because the head of the Madrasah is required to have various abilities, both in the fields of management and leadership style. In addition, the governance of the Al-Ihlas Madrasah itself is adjusted to follow government regulations regarding management in madrasah management, the madrasah curriculum system, management of teacher strategies in teaching, and management of madrasah facilities and infrastructure.